Environmental magnetic record of paleoclimate, unroofing of the Transantarctic Mountains, and volcanism in late Eocene to early Miocene glaci‐marine sediments from the Victoria Land Basin, Ross Sea, Antarctica. Issue 5 (6th May 2013) - Roberts, Andrew P.; Sagnotti, Leonardo; Florindo, Fabio; Bohaty, Steven M.; Verosub, Kenneth L.; Wilson, Gary S.; Zachos, James C.
Abstract : [1] We synthesize environmental magnetic results for sediments from the Victoria Land Basin (VLB), which span a total stratigraphic thickness of 2.6 km and a ~17 Myr age range. We assess how magnetic properties record paleoclimatic, tectonic, and provenance variations or mixtures of signals resulting from these processes. The magnetic properties are dominated by large‐scale magnetite concentration variations. In the late Eocene and early Oligocene, magnetite concentration variations coincide with detrital smectite concentration and crystallinity variations, which reflect paleoclimatic control on magnetic properties through influence on weathering regime; high magnetite and smectite concentrations indicate warmer and wetter climates and vice versa. During the early Oligocene, accelerated uplift of the Transantarctic Mountains gave rise to magnetic signatures that reflect progressive erosion of the Precambrian‐Mesozoic metamorphic, intrusive, and sedimentary stratigraphic cover succession associated with unroofing of the adjacent Transantarctic Mountains. From the early Oligocene to the early Miocene, a consistent fining upward of magnetite particles through the recovered composite record likely reflects increased physical weathering with glacial grinding contributing to progressively finer grained Ferrar Dolerite‐sourced magnetite. After 24 Ma, the magnetic properties of VLB sediments are primarily controlled by the weathering and erosion of McMurdo Volcanic Group rocks; increased volcanic glass contents contribute to the fining upward of magnetite grain size. Overall, long‐term magnetic property variations record the first‐order geological processes that controlled sedimentation in the VLB, including paleoclimatic, tectonic, provenance, and volcanic influences. Key Points: We synthesize Antarctic environmental magnetic results for a 17 Ma period Late Eocene ‐ early Oligocene variations were controlled by climate Transantarctic Mountain unroofing and volcanism controlled later variations